Atmosphärische Transporte und raumzeitliche Verteilung von Mikroschadstoffen (Spurenmetalle, Organochlorpestizide, polyzyklische aromatische Kohlenwasserstoffe) in Nordostbayern - Hermann, Reimer (ERDKUNDE, 1984)
The combination of predominant westerly winds with north south running mountain barriers causes an increase of micro pollutant immission with increasing height and luff-lee effect. It can be shown that long distance transport contributes a great deal to the overall pollution. Turbulent transport near the ground causes a regional distribution characterized by a decrease of micropollutant immissions within a short distance from the emission source. This pollution pattern is overlaid by a pattern originating from the long distance transport. Therefore, trace metals and PAH (polycyclic aromatic hydrocarbons) show similar distribution patterns with high concentrations in densely populated areas and increasing concentrations along the mountain ridges.Singular emission sources (e.g. for lead) can easily be detected. In comparison to the two former groups of micropollutants,organo-chlorine pesticides show a less distinct distribution pattern which can be explained by their diffuse emission sources. Since the beginning of industrialization trace metal pollution in NE-Bavaria has increased considerably: the amount of zinc has multiplied by two and that of lead and cadmium even by four. Seasonal variations of weather conditions and emissions of micro pollutants result in a different seasonal immission pattern: trace metals and PAH show a distinct maximum in winter, the organo chlorine pesticides in summer.